Quantification of Oligomeric Proanthocyanidins in Grapes Seed Extract by Spectrophotometric Method - Shivaprasad, H.N.; Khanam, Salma (Asian Journal of Chemistry, 2010)
Oligomeric proanthocyanidin complexes are naturally occurring plant metabolites widely available in fruits, vegetables, nuts, seeds, flowers and bark. Proanthocyanidins belong to the category known as condensed tannins, one of the two main categories of plant tannins. In the present communication we have developed a simple UV spectrophotometric method for the analysis of proanthocyanidins in grape seed extract.